The disposition effect and the relevance of the reference period : evidence among sophisticated investors (2019)
The Disposition Effect (DE) describes the disposition of selling winners too early and of keeping losers for too long. Conventionally the DE is measure using trades and the average purchase price. Being more rigorous with its measure, we found that US institutional and mutual fund present some evidence of DE when we used trades as the unit of measurement for both type of agents, but if we used dollars value as the unit of measurement, the DE vanishes as the time window becomes more distant. This reflects that the DE is a short term phenomenon that requires to consider how the reference periods are form but also which unit of measure are used. Considering this, we found that the market participants with the highest DE tend, on average, to be those with lower cumulative return, have smallest value portfolios, last the least, and have the highest coefficient of variation.